Exploring Technology Adoption and SAK EMKM Adherence among MSMEs in the Borobudur Area - Nilasari, Ayunda Putri; Anis Chariri (Universitas Muhammadiyah Yogyakarta, 2026)
This research aims to investigate the level of IT adoption and compliance with SAK EMKM. A qualitative interpretive phenomenological paradigm was employed to explore the level of IT adoption and compliance with SAK EMKM in the financial reporting of MSMEs in the Borobudur area. The results disclosed the low level of IT adoption and compliance caused by SAK EMKM being too complex, irrelevant to the business scale, and having limited resources and low technical capabilities. This research contributes to the accounting research literature, revealing the perspectives of SAK EMKM, as well as integrating IT adoption with applicable standards, particularly in the Borobudur area.